Strengthening the education sector response to HIV&AIDS in the Caribbean - Bundy, Donald A. P. 1993-; Fontani, Paolo; CARICOM Strategy in Education and HIV&AIDS; UNESCO; Weltbank (World Bank working paper, 2008)
In June 2006, Ministers of Education and representatives of National AIDS Authorities met in Port-of-Spain, Trinidad and Tobago, under the auspices of the CARICOM Council on Human and Social Development, and agreed to promote education sector leadership in addressing HIV and AIDS and to create a supportive policy and financial environment at national and regional levels. This report describes the development of these regional processes and how they have led to a stronger education sector response at the regional level. It also focuses on developments in three countries (Guyana, Jamaica, and St. Lucia) as examples of how this regional effort translates into action at the national level